2009
DOI: 10.1080/13825580802573052
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the use of Study Context to Increase Recollection

Abstract: We examined how context presented at study affects recollection of words in younger and older adults. In Experiment 1, participants studied words presented with a picture of a face (context-rich condition) or a rectangle (context-weak condition), and subsequently made 'Remember', 'Know', or 'New' judgments to words presented alone. Younger, but not older, adults showed higher Remember accuracy following rich- than weak-context trials. In Experiment 2, we manipulated the type of processing engaged during the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…For example, Staresina, Gray, and Davachi (2009) found that congruent items resulted in better memory for items and item-colors relative to incongruent items. However, if such congruency effects depend on effortful encoding strategies or attentional resources, older adults, who show deficits in self-initiated strategy use (Craik & Byrd, 1982;Skinner & Fernandes, 2009), might be less likely to use such factors. Indeed, older adults need additional environmental support to engage in more effortful strategies (Hay & Jacoby, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Staresina, Gray, and Davachi (2009) found that congruent items resulted in better memory for items and item-colors relative to incongruent items. However, if such congruency effects depend on effortful encoding strategies or attentional resources, older adults, who show deficits in self-initiated strategy use (Craik & Byrd, 1982;Skinner & Fernandes, 2009), might be less likely to use such factors. Indeed, older adults need additional environmental support to engage in more effortful strategies (Hay & Jacoby, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Across 49 published papers, we identified 68 independent comparisons of young and older adults (see Table 1). We treated each experiment in a multiple-experiment report as an independent observation when a new sample of participants were recruited (e.g., Healy et al 2005; Jennings and Jacoby 1993; Luo et al 2007; McCabe and Geraci 2009; Parks 2007; Skinner and Fernandes 2009a). Likewise, experiments that employed a between-subject manipulation crossed with age were treated as providing two independent observations (e.g., McCabe and Geraci 2009; Toth and Parks 2006).…”
Section: Methodsmentioning
confidence: 99%
“…We made this distinction based on the types of materials used during the test phase. For example, a study that included words paired with a picture (Luo et al 2007) or a face (Skinner and Fernandes 2009a), but only tested memory of the words was coded as a study using verbal materials. The type of nonverbal materials used in the studies included in the effect size analysis included travel scenes (Düzel et al 2011; Howard et al 2006), objects (Angel et al 2013; Duarte et al 2006), and symbols (Friedman et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It would be interesting for follow-up studies to employ these techniques in a recognition task to test whether faces with greater similarity yield more false alarms in older adults. It might also be possible to combine morphing techniques with experimental manipulations borrowed from studies on source memory (e.g., Brown et al, 1995 ; Skinner and Fernandes, 2009 ; Rahhal et al, 2002 ; Luo et al, 2007 ) to examine if manipulations of the context under which a face was viewed has a differential impact on younger and older adults. Finally, because face recognition deficits in older adults have deleterious implications for eyewitness testimonies, further investigations into techniques that could improve recollecting contextual information via cues to source memories are worth pursuing.…”
Section: Decline In the Recollection Of Contextual Informationmentioning
confidence: 99%